2019
DOI: 10.1590/1678-4162-9805
|View full text |Cite
|
Sign up to set email alerts
|

Suplementação proteica de vacas leiteiras mantidas em pastagem de Tifton 85 durante o período de seca

Abstract: RESUMO Concentrados com alta proteína bruta e minerais e com menor concentração de energia poderiam ser utilizados em menores quantidades no balanceamento de dietas com volumosos tropicais. Assim, objetivou-se avaliar o consumo de matéria seca, a resposta produtiva e econômica de vacas da raça Girolando mantidas em pastagem de Tifton 85 durante o período de seca, as quais receberam diferentes concentrações de suplementação proteica. Foram utilizadas 12 vacas da raça Girolando em lactação, com produção de leite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…The comparison demonstrates that Tifton 85 developed in VFCW produces less crude fibre, which can improve animal production because of the higher digestible portion in the forage. Concentrates with high CP and mineral content, and low energy concentration, could be used in small quantities to balance tropical pasture diets (Teixeira et al 2019). The CP content is calculated from the nitrogen content of the food by sulphuric acid digestion, which converts to ammonia all nitrogen present in the sample, except that in the form of nitrate and nitrite (McDonald et al 2011).…”
Section: Tifton 85 Fibre Development In Vfcwmentioning
confidence: 99%
“…The comparison demonstrates that Tifton 85 developed in VFCW produces less crude fibre, which can improve animal production because of the higher digestible portion in the forage. Concentrates with high CP and mineral content, and low energy concentration, could be used in small quantities to balance tropical pasture diets (Teixeira et al 2019). The CP content is calculated from the nitrogen content of the food by sulphuric acid digestion, which converts to ammonia all nitrogen present in the sample, except that in the form of nitrate and nitrite (McDonald et al 2011).…”
Section: Tifton 85 Fibre Development In Vfcwmentioning
confidence: 99%
“…Cultivated pastures form the basis for milk production and, when well managed, are capable of sustaining satisfactory levels of milk production, especially at the most favorable times of the year (Teixeira et al, 2019;Santana et al, 2019;Borges et al, 2020). However, throughout the year, forage production fluctuates according to climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In beef cattle, the practice of using protein supplements associated with deferred pasture is common, and has positive results for weight gain, since it improves the digestibility of the pasture forage mass and forage intake (Sampaio et al, 2017). Currently, for dairy cows in Brazil, it is observed that about 90% of concentrated supplements have between 20 and 22% of crude protein, and the most common recommendation is to provide one kg of concentrate for every three kg of milk produced (Sheahan et al, 2013;Teixeira et al, 2019). However, only good quality pasture is generally not enough to promote the full productive potential of highyielding cows, since it does not meet the entire requirement of the dairy animal, especially in terms of energy (Teixeira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, feed intake, digestibility and animal productive performance are generally low (EUCLIDES et al, 2009). Supplementation aims to complement the diet providing nutritional elements, such as energy, protein, minerals, and vitamins that are lacking or in insufficient quantities to meet the animal requirements (TEIXEIRA et al, 2019;WASSIE et al, 2019).…”
Section: Pasture Cattle Supplementationmentioning
confidence: 99%